Sistem Informasi Data Alumni SMK Negeri 2 Pangkalpinang Berbasis Website - Sanjaya, Rio; Fujiyanti, Linda; Afriansyah, Riki (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
One of the largest SMKs in the Bangka Belitung Islands is SMK Negeri 2 Pangkalpinang. At SMK Negeri 2 Pangkalpinang, alumni registration is still done with a Google form that can't be edited in the event of a data collection error, which can make the administration's validation process more difficult. The process of collecting alumni data, therefore, requires a more efficient system. The creation of a SMK Negeri 2 Pangkalpinang alumni data system is the goal of this study. This study used observation, interviews, and data collection about the alumni data collection information system at SMK Negeri 2 Pangkalpinang to collect the data. The waterfall development method is used to create the system. The development of a website-based alumni data information system for SMK Negeri 2 Pangkalpinang that is capable of managing alumni data and assisting the administration in processing alumni data is the outcome of this study. The user satisfaction survey found that 81.2% of respondents agreed that the system works well.